I have a Body, I am a Body: somatic approaches to movement at an undergraduate dance course - Gravina (Universidade Federal de Santa Maria, UFSM, Santa Maria, Brazil), Heloisa Corrêa (Revista Brasileira de Estudos da Presença, 2022)
In this article, I started from the experience of somatic approaches to movement at the undergraduate dance course of the Universidade Federal de Santa Maria to propose a discussion about the pedagogical and artistic implications of this choice. I explain my point of view as a teacher and artist, as well as my understanding of the use of somatic approaches to dance, and explore the students’ experiences. Within the framework of performance as an analytical paradigm, articulated from the viewpoint of Somaesthetics, I point out some ways provided by such a choice in promoting emancipatory pedagogical practices and expanding the artistic possibilities of dancers.